Economic Diplomacy Strategy for Nepal - Parajuli, Chhabindra (Prashasan: The Nepalese Journal of Public Administration, 2025)
Economic diplomacy has emerged as a crucial aspect for promoting inward Foreign Direct Investment (FDI), facilitating international trade, and enhancing tourism. While the Government of Nepal has implemented various instruments for these purposes, achievements in these specific sectors have not been satisfactory. Economic diplomacy should be given the highest priority, extending its reach across all government spheres. The main focus of economic diplomacy is to attract foreign businesses, investments, new and enhanced technologies, and tourists. Economic diplomacy is closely connected with political, public, and other segments of diplomatic work. The objectives of economic diplomacy can be achieved through meaningful and active engagement with a wide range of concerned stakeholders, including government agencies and private sector umbrella organizations. The major concern today is how to prepare and implement a robust economic diplomacy strategy to reap better economic benefits from bilateral, regional, and global mechanisms as well as engagements, in order to achieve the nation's economic development vision. The economic diplomacy strategy should be supported and equipped with relevant programs and activities by all concerned agencies. The capacity enhancement of government agencies and private sectors should also be strengthened in line with targeted actions and focused areas of intervention. The economic diplomacy strategy would be backed by dedicated budgets from all relevant ministries, with suitable programs, activities, and events. The economic diplomacy strategy would support achieving milestones such as the reduction of the country's ballooning trade deficit, enlargement of market access opportunities for Nepali products abroad, attraction of more inward foreign investment, integration of domestic production networks into regional and global networks, facilitation of technology transfer into domestic industries, and expansion of investment- and trade-related infrastructure. Spanning from hydropower and renewable energy to sustainable eco-tourism and agriculture, as well as from the service sector to manufacturing, Nepal offers diverse and lucrative investment avenues for investors. Recently, Nepal has made significant improvements in legal, institutional, and procedural reforms to create a conducive business environment.